Pelvic Radiation Improves Local Control After Hysterectomy for Uterine Leiomyosarcoma: A 20-Year Experience. Issue 6 (1st July 2009) - Mahdavi, Ali; Monk, Bradley J.; Ragazzo, Jennifer; Hunter, Mark I.; Lentz, Scot E.; Vasilev, Steven A.; Tewari, Krishnansu S.
Abstract : Background: Uterine leiomyosarcoma (LMS) is associated with high rate of recurrence after surgical resection. The role of adjuvant radiation therapy in improving survival in women with uterine LMS is unclear. Methods: All cases of LMS treated from 1985 to 2005 at 11 regional medical centers were identified. Kaplan-Meier survival curves were constructed and compared with log-rank testing. Multivariate analysis was performed to account for the potential influence of confounding factors. Results: One hundred forty-seven patients with LMS were identified. The median age of diagnosis was 51 years with the stage distribution of stage I (n = 87), II (n = 9), III (n = 25), IV (n = 25), and unknown (n = 1). One hundred forty-three underwent total abdominal hysterectomy and bilateral salpingoophorectomy. Twenty-four (17%) of these patients received adjuvant pelvic irradiation, and 63 (44%) received adjuvant and/or palliative chemotherapy. With a median follow-up of 24 months (range, 1-249 months), the median survival for the entire group was 37 months. Cox proportional hazards modeling demonstrated the presence of high tumor grade and advanced stage adversely affected survival. Although the 5-year survival for patients who received adjuvant radiotherapy was significantly higher than those who did not (70% vs 35%), this survival advantage was not sustained as the curves crossed at 90-month follow-up. Pelvic recurrence rate was lower in the radiation group (18% vs 49%; P = 0.02). Conclusions: Adjuvant radiation therapy was associated with decreased pelvic failure and a modest improvement in 5-year survival, but did not impact overall survival with extended follow-up.